The advent of chimeric antigen receptor T Cell therapy in recalibrating immune balance for rheumatic autoimmune disease treatment - Guo, Qianyu; Li, Jie; Wang, Juanjuan; Li, Linxin; Wei, Jia; Zhang, Liyun (Frontiers in Pharmacology, 2024)
CAR-T cell therapy, a cutting-edge cellular immunotherapy with demonstrated efficacy in treating hematologic malignancies, also exhibits significant promise for addressing autoimmune diseases. This innovative therapeutic approach holds promise for achieving long-term remission in autoimmune diseases, potentially offering significant benefits to affected patients. Current targets under investigation for the treatment of these conditions include CD19, CD20, and BCMA, among others.However, CAR-T therapy faces difficulties such as time-consuming cell manufacturing, complex and expensive process, and the possibility of severe adverse reactions complicating the treatment, etc. This article examines CAR-T therapy across various rheumatic autoimmune diseases, including systemic lupus erythematosus (SLE), rheumatoid arthritis (RA), Sjögren's syndrome (SS), systemic sclerosis (SSc), antisynthetase syndrome (ASS), and ANCA-associated vasculitis (AAV), highlighting both therapeutic advancements and ongoing challenges.